Optimalisasi Digital Marketing Dalam Pemanfaatan Canva Bagi Pelaku UMKM di 26 Ilir Kota Palembang - Putri, Intan; Syukerti, Nanda; Mulyadi, Ahmad Iman; Puspita, Hilda; Zuliansyah, Muhammad Andri (LPPM UMRI, 2024)
It turns out that the large opportunity for using social media as product promotion cannot be fully utilized by UMKM. Most of them do not understand the benefits and important role of online media, have difficulty creating attractive promotional image content, have limited knowledge of application technology, and have limited creativity in graphic design. Attractive promotional content is one of the main keys to digital marketing. Canva is an application technology that offers convenience in graphic design. The existence of the Canva application can certainly be utilized by UMKM in creating image content as product promotion because its use is relatively easy. Implementation of community service activities is carried out face to face using digital learning methods and active learning using project based learning as additional media. This activity was attended by the community as UMKM actors under the auspices of the 26 Ilir Literacy Village, Palembang City.